Soil quality of a rice organic farm in Langkong, M'lang Cotabato - Cedeño, Kathleen C. (Southeastern Philippines Journal of Research and Development, 2019)
Soil quality is crucial to global food production security. However, research data on soil quality which is vital to enhancing soil fertility and crop yield, is limited particularly on the soil in the rice fields located in Langkong, Mlang, Cotabato. This study aims to assess the soil quality of one of the organic rice farms in said area. Soil samples were collected in thirty-one (31) paddies for two sampling periods: thirty (30) days after harvest and thirty (30) days after rice transplanting. Eight (8) soil indicators representing soil physicochemical characteristics were measured from 0-15 cm depth; the indicators were soil texture, water holding capacity, pH, exchange phosphorus, extractable potassium, total organic matter, electrical conductivity and cation exchange capacity. Results reveal that soils in the studied area are characterized by clay loam with moderate water-holding capacity of about 62.57% and 60.57% for both sampling periods respectively. The soil is strongly acidic (5.3 and 5.5) and has a low amount of organic matter (2.16% and 1.57%) and exchangeable P (8.55 ppm and 2.48 ppm), although it has marginal extractable K (80.77 ppm and 91.10 ppm). Also the soils are non-saline and have low cation exchange capacity. The findings signify that the soils have insufficient fertility to sustain the optimal growth of the rice plants which can potentially reduce the yield of rice production.Thus, amendment of the soil quality and enhancement of soil management practices should be taken into consideration for further improve soil fertility to ensure productivity and profitability of farmers.